PERAN NILAI-NILAI AL ISLAM DAN KEMUHAMMADIYAHAN DALAM PENCEGAHAN FRAUD PADA AMAL USAHA MUHAMMADIYAH KOTA PALOPO - AMRAN, HIKMAL; Antong; Rahmawati (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to analyze the role of Al-Islam and Kemuhammadiyahan (AIK) values, which include Ash-Shiddiq (honesty), Al-Iltizam (commitment), and Amanah (responsibility), in preventing fraud within Muhammadiyah Business Enterprises (AUM) in Palopo City. Using a quantitative approach, the research employed a survey method with questionnaires distributed to 50 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS software. The results show that the three independent variables—Ash-Shiddiq, Al-Iltizam, and Amanah—positively and significantly influence fraud prevention. Ash-Shiddiq contributes by fostering a culture of honesty that enhances transparency and reduces the rationalization of fraudulent acts. Al-Iltizam strengthens commitment to sharia principles and organizational ethics, thereby minimizing opportunities for fraud. Meanwhile, Amanah instills a strong sense of moral responsibility, helping individuals reduce the pressure to commit fraud. This study supports the Fraud Triangle theory by demonstrating that AIK values can effectively mitigate the main elements of fraud: pressure, opportunity, and rationalization. The implications of this research emphasize the importance of strengthening religious values within organizations, coupled with robust internal control systems, to create an anti-fraud culture. This study recommends regular training, strict supervision, and the implementation of AIK-based anti-fraud policies to support the sustainability of AUM as an organization with integrity. Keywords: Al-Islam and Kemuhammadiyahan, Ash-Shiddiq, Al-Iltizam, Amanah, Fraud Prevention.